Operational Risk Management in Digital Banks: Challenges and Solutions - Widjanarko, Wirawan; Manurung, Adler Haymans; Machdar, Nera Marinda (Dinasti Publisher, 2025)
The purpose of this research is to see the effect of system uptime and compliance regulations on operational risk management in digital banks (cybersecurity). The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct literature reviews of relevant previous articles. The data used in this research is secondary data, sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) System uptime affects Cyber Security at Digital Banks; and 2) Regulatory compliance affects Cyber Security in Digital Banks